Effect of Coffee Extracts with Different Roasting Degrees on Lipid Metabolism and Gut Microbiota in High-Fat Fed Mice - WANG Chunhua, XIAO Ying, SUN Bin, PAN Liang, LIU Jieying, JIANG Yongying, ZHOU Yiming, YE Lin, LIU Xiaojie (Shipin Kexue, 2025)
This study aimed to explore the intervention effects of coffee extracts with different roasting levels on lipid metabolism disorders and gut microbiota in high-fat diet mice. Specifically, 45 C57BL/6J male mice were randomly divided into five groups, which were fed a control diet (CON), a high-fat diet (HFD) alone and supplemented with lightly roasted (LC), moderately roasted (MC) and highly roasted (HC) coffee extracts, respectively for 9 weeks. After completion of the experimental period, changes in body mass and blood lipids were determined and the composition of the gut microbiota was identified using 16S rRNA gene sequencing. The results demonstrated that highly roasted coffee showed significantly better ameliorative effects on obesity, dyslipidemia and inflammatory reactions compared with moderately and lowly roasted coffee (P < 0.05). The gut microbiota diversity analysis showed that highly roasted coffee significantly increased the ratio of relative abundance between Firmicutes and Bacteroidetes in HFD-fed mice and promoted the enrichment of probiotics such as Oscillospirales and Odoribacter. Meanwhile, it significantly increased the production of short-chain fatty acids (P < 0.05), compared with the high-fat diet-fed group. Additionally, highly roasted coffee was significantly more effective in up-regulating the mRNA expression of the colonic tight junction protein Claudin-1 than moderately and lowly roasted coffee (P < 0.05). In summary, highly roasted coffee had more significant intervention effects on obesity, and this may be attributed to the structural regulation of the gut microbiota.